2021
DOI: 10.1002/aenm.202100901
|View full text |Cite
|
Sign up to set email alerts
|

A New Approach to Stable Cationic and Anionic Redox Activity in O3‐Layered Cathode for Sodium‐Ion Batteries

Abstract: Research data are available upon request.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
23
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 36 publications
(24 citation statements)
references
References 67 publications
1
23
0
Order By: Relevance
“…However, SIBs show great promise in the applications where cost and sustainability are top priority, such as large‐scale energy storage. [ 5–9 ]…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, SIBs show great promise in the applications where cost and sustainability are top priority, such as large‐scale energy storage. [ 5–9 ]…”
Section: Introductionmentioning
confidence: 99%
“…However, SIBs show great promise in the applications where cost and sustainability are top priority, such as large-scale energy storage. [5][6][7][8][9] Like LIBs, cathode materials are also the main factor limiting the energy density and cost of SIBs. Finding suitable sodium intercalation hosts is pressing.…”
mentioning
confidence: 99%
“…[ 8–10 ] Interestingly, such oxygen behavior is also applicable to not only Na‐rich cathodes, [ 11–13 ] which are an analog of Li‐rich materials, but also Na‐deficient TM oxides. [ 14–21 ] The Na‐rich compounds are mainly based on noble and expensive TMs, such as 4 d (Ru) and 5 d (Ir) metals; [ 22–24 ] however, Na‐deficient materials (P2 and P3) are represented by abundant and low‐cost 3 d (Mn). [ 15,16 ] There is a universal notation for oxygen redox: Na x [A y TM 1− y ]O 2 , where TM is Mn, [ 14–20 ] Ru, [ 21,25,26 ] or Ir, [ 23,27,28 ] and A is monovalent Li [ 14,17,18,29,30 ] or divalent Mg [ 20,31–33 ] or Zn.…”
Section: Introductionmentioning
confidence: 99%
“…[8][9][10] Interestingly, such oxygen behavior is also applicable to not only Na-rich cathodes, [11][12][13] which are an analog of Li-rich materials, but also Na-deficient TM oxides. [14][15][16][17][18][19][20][21] The Na-rich compounds are mainly based on noble and expensive TMs, such as 4d (Ru) and 5d (Ir) metals; [22][23][24] however, Na-deficient materials (P2 and P3) are represented by abundant and low-cost 3d (Mn). [15,16] There is a universal notation for oxygen redox:…”
mentioning
confidence: 99%
“…The most commonly used synthesis method is the solid-state method, which is mainly due to its simple preparation process and easy operation. [34][35][36][37][38] For example, Wang et al 35 used NaCH 3 COOH as the sodium source, mixed it with a certain stoichiometric ratio of K 2 CO 3 and MnO 2 , ball milled for 12 hours, and added a small amount of acetone as a dispersant to make the materials uniformly mixed. The dried powder is calcined at a high temperature to obtain the P2-Na 0. material, it can be found that the sodium content and synthesis temperature have a great impact on the phase of the material.…”
Section: Preparation Of Layer-structured Oxidesmentioning
confidence: 99%